The Process of Acculturation of the Kazakh Diaspora in the USA - Saiyn Жазира (Turkic Studies Journal, 2023)
In the context of globalization, millions of people belonging to different cultures and ethnic groups have been given the opportunity to move freely around the world and engage in cultural exchanges with other peoples. In the largest cities of the world, the number of migrants from foreign countries is constantly increasing, and along with this the number of problems is increasing. The number of migrants in the world amounted to 272 million people, or 3.5% of the world’s population. By 2050, this figure could reach 400 million (UN DESA Report, 2019 https://www.un.org/ru/desa). These migrations often lead to misunderstandings, and sometimes to conflict between representatives of the two cultures. According to J. Berry (1997), in the period when some countries are striving for political and economic integration, while others, on the contrary, for independence, the situation of cultural interaction becomes especially acute. Therefore, scholars and individuals who somehow come into contact with the process of intercultural communication, attach special importance to the study of these processes, one of which is acculturation. This article examines the acculturation process of Kazakhs living in the United States, gives the concept of such forms of acculturation as segregation, assimilation, integration and marginalization.